Transformational Leadership, Compensation, Career Development, & Job Satisfaction: Key Factors in Employee Performance in the F&B Industry - Kadek Dina Yuliastari; Gede Sri Darma (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The Food and Beverage (F&B) industry in Indonesia, especially in Bali, is experiencing rapid growth that contributes significantly to the country's Gross Domestic Product (GDP). This study aims to understand the factors that influence employee performance at Makanan Minuman Korporindo, which manages three restaurants in Badung Regency, Bali. This study uses a quantitative approach with Structural Equation Modeling (SEM) through Partial Least Squares (PLS) to analyze data from 160 employees. The results show a significant relationship between transformational leadership, compensation, career development, job satisfaction, and employee performance. Transformational leadership has a positive impact on employee job satisfaction and performance. Likewise, compensation and career development significantly affect job satisfaction. Job satisfaction mediates the relationship between these variables and employee performance and shows a strong indirect effect. This study contributes to the literature by confirming the important role of transformational leadership, adequate compensation, and career development in improving employee satisfaction and performance in the F&B sector. These findings emphasize the importance of creating a supportive work environment to maximize employee potential and organizational success.